INCREASED DNA METHYLTRANSFERASE 1 (DNMT1) GENE EXPRESSION IN HUMAN LYMPHOMAS BY FLUORESCENT IN SITU HYBRIDIZATION - Qayum, Iftikhar; Ashraf, Muhammad (Journal of Ayub Medical College Abbottabad, 2004)
Background: The DNA Methyltransferase 1 (DNMT1) gene is among the better known '˜epigenetic' systems that can regulate normal and abnormal gene expression as well as create '˜hot spots' for DNA mutations. Its role has been studied in a number of malignancies with important implications for involvement in early events of malignant transformation. The present study describes the findings with respect to expression of this gene in human lymphomas studied by Fluorescent In Situ Hybridization (FISH). Method: The study was undertaken on randomly selected archival human lymph nodes comprising 50 specimens of normal or reactive lymph nodes and 50 specimens of lymphoma lymph nodes. These were subjected to FISH using oligonucleotide Antisense probes for the DNMT1 mRNA according to standard FISH protocols. Percent cells stained, mean '˜dots' stained per cell and staining signal intensity were taken as the criteria for comparing control and lymphoma lymph nodes. Quantitation of probe signals was done both by manual visualisation of the fluorescent signals and computer based image analysis. Results: Data indicated a significantly increased expression of the DNMT1 mRNA in lymphoma cases as compared to controls (p<0.001). Conclusion: This implies a possible role of the DNMT1 gene in transformation / oncogenesis in human lymphomas. Key Words: DNA methyltransferases, FISH, lymphomas.